1994
DOI: 10.1111/j.1365-2141.1994.tb05063.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐3 is an autocrine growth factor of human megakaryoblasts, the DAMI and MEG‐01 cells

Abstract: Interleukin-3 (IL-3), a cytokine known to be produced by activated T lymphocytes, mast cells, eosinophils and neutrophils, is a potent stimulator of normal haemopoiesis, particularly megakaryocytopoiesis. However, it remains unknown whether leukaemic megakaryoblasts can produce IL-3 and whether IL-3 is involved in the pathological process of megakaryoblastic leukaemia. In this study, several human leukaemia cell lines with or without megakaryocytic features, the DAMI, MEG-01, HEL, K562, HL-60 and U937, were ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…A number of previous in vitro studies have demonstrated that a substantial proportion of fresh leukemic blasts or leukemic cell lines may produce hematopoietic growth factors, bear receptors for the produced factors, and be growth inhibited by neutralization of the produced factors [13][14][15][16][17][18][19]. Our studies extend these observations by demonstrating that AML14.3D10 cells use endogenously produced GM-CSF to activate intracellular GM-CSFrelated signal transduction pathways.…”
Section: Discussionsupporting
confidence: 78%
“…A number of previous in vitro studies have demonstrated that a substantial proportion of fresh leukemic blasts or leukemic cell lines may produce hematopoietic growth factors, bear receptors for the produced factors, and be growth inhibited by neutralization of the produced factors [13][14][15][16][17][18][19]. Our studies extend these observations by demonstrating that AML14.3D10 cells use endogenously produced GM-CSF to activate intracellular GM-CSFrelated signal transduction pathways.…”
Section: Discussionsupporting
confidence: 78%
“…On the other hand, List and colleges recently showed that inhibition by PSC 833 of the ABC1 transporter interrupts the efflux of IL-1β form leukemia cells and causes apoptosis which is avoided by exogenous substitution of IL-1β [171]. It is also known that both IL-3 and IL-6 may act as endogenous growth factors in autonomously growing leukemic cell lines [177,178], and endogenously produced GM-CSF may promote growth of malignant hematopoietic cells by secretion and binding to surface GM-CSF receptors [179]. Therefore, there are several candidates for a growth regulatory molecule working in an autocrine loop maintained by Pgp, but at present no study has provided proof of such a mechanism or identified the effector molecule.…”
Section: Inhibition Of P-glycoprotein May Trigger Apoptosismentioning
confidence: 99%
“…On the other hand, List and colleagues 37 have demonstrated that inhibition by PSC 833 of the ABC1 transporter interrupts the efflux of IL-1␤ from cultured leukemia cells and causes apoptosis, which is avoided by exogenous substitution of IL-1␤. It is also known that both IL-3 and IL-6 may act as endogenous growth factors in autonomously growing leukemic cell lines, 45,46 and endogenously produced GM-CSF may promote growth of malignant hematopoietic cells by secretion and binding to surface GM-CSF receptors. 47 Therefore, there are several candidates for a growth regulatory molecule working in an autocrine loop maintained by Pgp, but at present no study has provided proof of such a mechanism or identified the effector molecule.…”
Section: Figurementioning
confidence: 99%